1981
DOI: 10.1037/0022-006x.49.4.554
|View full text |Cite
|
Sign up to set email alerts
|

Sequential analysis of conflict and accord in distressed and nondistressed marital partners.

Abstract: The interactional patterns of distressed (n = 22) and nondistressed (« = 17) couples were compared through base rate and sequential analyses of communication samples that were coded with the Marital Interactional Coding System. Nondistressed, compared to distressed, couples emitted higher rates of problem-solving, verbal and nonverbal positive, and neutral behaviors. Sex differences were found for Nonverbal Positive and Neutral behaviors. The sequential analyses provided support, but of limited duration, for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
195
1
10

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(216 citation statements)
references
References 17 publications
(37 reference statements)
10
195
1
10
Order By: Relevance
“…Gottman's (1979) widely cited findings show that although all of his couples tend to show reciprocity in hostile affect in discussions about common problems in their marriages, the less welladjusted showed greater reciprocity in hostile affect than did the better adjusted couples. These findings have been replicated by Margolin and Wampold (1981). Pike and Sillars (1985) also found greater reciprocity in negative vocal affect for dissatisfied as opposed to satisfied married couples.…”
Section: Research On Coordination and Interpersonal Outcomesupporting
confidence: 70%
“…Gottman's (1979) widely cited findings show that although all of his couples tend to show reciprocity in hostile affect in discussions about common problems in their marriages, the less welladjusted showed greater reciprocity in hostile affect than did the better adjusted couples. These findings have been replicated by Margolin and Wampold (1981). Pike and Sillars (1985) also found greater reciprocity in negative vocal affect for dissatisfied as opposed to satisfied married couples.…”
Section: Research On Coordination and Interpersonal Outcomesupporting
confidence: 70%
“…For example, anger might not belong in the same category as sadness, and different specific affects might not necessarily function in the same way in a marital interaction (Gottman & Levenson, 1986). The observational use of microanalytic codes may be useful in understanding the most consistent finding in the literature on marital interaction and marital satisfaction: the finding that negative interaction is much more common in the interaction of unhappily married couples than happily married couples, which has been reported in laboratories in the United States as well as in Europe (Gottman, 1979;Hahlweg, Revenstorf, & Schindler, 1984;Levenson & Gottman, 1983;Margolin & Wampold, 1981;Raush, Barry, Hertel, & Swain, 1974;Revenstorf, Hahlweg, Schindler, & Vogel, 1985;Schaap, 1982;Ting-Toomey, 1982). In these studies, negative content codes as well as affects (e.g., anger, contempt, disgust) have been lumped into this negative category.…”
mentioning
confidence: 97%
“…In these studies, negative content codes as well as affects (e.g., anger, contempt, disgust) have been lumped into this negative category. However, when most authors have interpreted their results, they have usually invoked images of a couple in conflict responding to one another with anger (see, for example, Revenstorf et al, 1985;Margolin & Wampold, 1981). However compelling these images seem, an analysis is needed that separates the global category of negative interaction into its components to determine whether anger is in fact the key to understanding marital distress.…”
mentioning
confidence: 99%
“…For example, in the domain of marital interactions, Margolin and Wampold (1981) showed that distressed partners tend more often to show a "negative reciprocity" than nondistressed couples, i.e. a negative action by one partner (a criticism, for example) is followed by a negative reaction by the other partner and so on.…”
Section: Advantages Of Observational Datamentioning
confidence: 99%